Randomized Controlled Trial of Minimally Invasive Sacroiliac Joint Fusion Using Triangular Titanium Implants vs Nonsurgical Management for Sacroiliac Joint Dysfunction: 12-Month Outcomes - Polly, David W.; Cher, Daniel J.; Wine, Kathryn D.; Whang, Peter G.; Frank, Clay J.; Harvey, Charles F.; Lockstadt, Harry; Glaser, John A.; Limoni, Robert P.; Sembrano, Jonathan N. (Neurosurgery, 2015)
BACKGROUND:Sacroiliac joint (SIJ) dysfunction is a prevalent cause of chronic, unremitting lower back pain. OBJECTIVE:To concurrently compare outcomes after surgical and nonsurgical treatment for chronic SIJ dysfunction. METHODS:A total of 148 subjects with SIJ dysfunction were randomly assigned to minimally invasive SIJ fusion with triangular titanium implants (n = 102) or nonsurgical management (n = 46). Pain, disability, and quality-of-life scores were collected at baseline and at 1, 3, 6, and 12 months. Success rates were compared using Bayesian methods. Crossover from nonsurgical to surgical care was allowed after the 6-month study visit was complete. RESULTS:Six-month success rates were higher in the surgical group (81.4% vs 26.1%; posterior probability of superiority > 0.9999). Clinically important (≥ 15 point) Oswestry Disability Index improvement at 6 months occurred in 73.3% of the SIJ fusion group vs 13.6% of the nonsurgical management group (P < .001). At 12 months, improvements in SIJ pain and Oswestry Disability Index were sustained in the surgical group. Subjects who crossed over had improvements in pain, disability, and quality of life similar to those in the original surgical group. Adverse events were slightly more common in the surgical group (1.3 vs 1.1 events per subject; P = .31). CONCLUSION:This Level 1 study showed that minimally invasive SIJ fusion using triangular titanium implants was more effective than nonsurgical management at 1 year in relieving pain, improving function, and improving quality of life in patients with SIJ dysfunction caused by degenerative sacroiliitis or SIJ disruptions. Pain, disability, and quality of life also improved after crossover from nonsurgical to surgical treatment. ABBREVIATIONS:EQ-5D, EuroQoL-5DINSITE, Investigation of Sacroiliac Fusion TreatmentMCS, mental component summaryNSM, nonsurgical managementODI, Oswestry Disability IndexPCS, physical component summaryRFA, radiofrequency ablationSF-36, Short Form-36SIJ, sacroiliac jointTTO, time trade-offVAS, visual analog scale